Correlation of Erectile Dysfunction and Lower Urinary Tract Symptoms among Men at Urology Clinic of a Tertiary Care Institute in South-East Nigeria - Joseph Amauzo Abiahu; Timothy Uzoma Mbaeri; Jideofor Chukwuma Orakwe; Alexander Maduaburochukwu Ekwunife Nwofor (Journal of Clinical and Diagnostic Research, 2020)
Introduction: Available literature suggests an association between Lower Urinary Tract Symptoms (LUTS) and sexual dysfunction especially Erectile Dysfunction (ED). LUTS, either alone or in combination with ED, represents a considerable problem for ageing men. An understanding of correlation between LUTS and ED in these ageing men will be useful in their routine care. Aim: To determine the incidence of ED and its correlation with LUTS in adult male patients attending the Urology clinic in a Tertiary Care Hospital. Materials and Methods: This was a cross-sectional study of 110 consecutive patients with LUTS recruited from the urological clinic. The data were collected, while ED and LUTS were assessed with the 5-Item Version of the International Index of Erectile Function (IIEF-5) and International Prostate Symptom Score (IPSS) questionnaire forms respectively. Findings were subjected to linear regression and Pearson’s chi-square tests, using Statistical Package for Social Sciences (SPSS) version 17. Results: The mean age of patients was 65.8±7.95 years. The incidence of ED among LUTS patients was 63.6%. There was positive correlation between ED scores and voiding phase, filling-storage phase and total LUTS scores. The severity of ED and graded LUTS score revealed no significant association between the severity of ED and that of voiding phase and fillingstorage phase LUTS. Conversely, severity of ED was significantly related to the severity of total LUTS score. Conclusion: ED is common amongst adult patients with LUTS. Its severity worsens with worsening LUTS. The management of patients with LUTS should therefore involve evaluation and treatment for ED. This calls for increased awareness of these conditions to both the doctor and the patient.